Critical Thinking In Learning Perspectives On Educational Philosophy - Pauzi, Pauzi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
Students are encouraged to enhance their analytical and evaluative skills through critical thinking, an essential component of education. This publication aims to investigate the significance of critical thinking in the context of learning, with a particular emphasis on educational philosophy views. This article examines the philosophical perspectives underpinning critical thinking, defines the relationship between those perspectives and academic goals, and assesses the impact these perspectives have on pupils' intellectual and moral growth. A method of research that takes a qualitative approach. Examining the ideas of epistemology, logic, and methodology that form the basis of critical thinking is accomplished through applying a philosophical perspective. To provide theoretical contributions to the debate over the function of critical thinking in the educational process, the discussion encompasses perspectives from ancient and modern philosophers. Additionally, the practical consequences of an educational philosophy perspective on the creation of curricula and teaching methods that support the development of critical thinking in students are discussed in this article.